First Non-Centrosymmetric Deca-Vanadoborate with Borate Vacancies, Self-Assembled Around a 1,3-Propanediammonium Cation - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Muñoz-Becerra, K; Muñoz-Becerra, K (American Chemical Society, 2015)
The first borate-vacant deca-vanadoborate of formula (NH3CH2CH2CH2NH3)5 [(NH3CH2CH2CH2NH3)V10B24O66H8]·13.23H2O with an occluded 1,3-propanediammonium cation, using molten methylboronic acid flux reaction is reported. This cluster lacks four borate units with respect to all known deca-vanadoborates. It crystallizes in the orthorhombic P21212 space group which is non-centrosymmetric, leading to the first non-centrosymmetric deca-vanadoborate reported in the literature. Even though the deca-vanadoborates formed by 28 borate units have an inner space large enough to host a molecule, no examples have been reported before. The electronic properties were studied using electronic spectroscopy, corroborating a fully reduced species, due to the lack of intervalence charge transfer transitions in the 1000 to 1500 nm region. The magnetic behavior provided evidence that the studied cluster presents strong antiferromagnetism among the ten VIV spin-carriers, with an S = 0 ground state. Using a model considering three different exchange pathways, three different J values were obtained, all of them antiferromagnetic in nature. © 2015 American Chemical Society.